Glass for magnetic recording medium substrate, magnetic recording medium substrate, magnetic recording medium, glass spacer for magnetic recording / reproducing device, and magnetic recording / reproducing device

Amorphous oxide glasses with specific compositions address the issues of deformation and surface smoothness in aluminum alloy substrates by providing high heat resistance and rigidity, enhancing the performance of magnetic recording media.

JP2024178387AActive Publication Date: 2024-12-24HOYA CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024166230
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-05-16
Filing Date
2024-09-25
Publication Date
2024-12-24
Estimated Expiration
2039-05-14

AI Technical Summary

Technical Problem

Aluminum alloy substrates used in magnetic recording media are prone to deformation and have insufficient surface smoothness, and there is a need for glass substrates with high heat resistance and rigidity to withstand high-temperature processing and reduce warpage and deflection in magnetic recording media.

Method used

Development of amorphous oxide glasses with specific compositions, including SiO2, Li2O, B2O3, MgO, and CaO, with a glass transition temperature of 650°C or higher and a Young's modulus of 90 GPa or higher, to provide excellent heat resistance and rigidity.

Benefits of technology

The developed glass substrates maintain high heat resistance and rigidity, ensuring the integrity of magnetic recording media during high-temperature processing and reducing deformation, enabling higher recording densities and improved surface smoothness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178387000001
    Figure 2024178387000001
  • Figure 2024178387000002
    Figure 2024178387000002
  • Figure 2024178387000003
    Figure 2024178387000003
Patent Text Reader

Abstract

To provide a glass for a magnetic recording medium substrate having excellent heat resistance and rigidity, a magnetic recording medium substrate made of the glass, a magnetic recording medium including the substrate, and a glass spacer for a magnetic recording device.SOLUTION: A glass for a magnetic recording medium substrate is an amorphous oxide glass having a SiO2 content of 56 to 80 mol%, a Li2O content of 1 to 10 mol%, a B2O3 content of 0 to 4 mol%, a total content of MgO and CaO (MgO+CaO) of 9 to 40 mol%, a specific gravity of 2.75 g / cm3 or less, a glass transition temperature of 650°C or more, and a Young's modulus of 90 GPa or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass for a magnetic recording medium substrate, a magnetic recording medium substrate, a magnetic recording medium, a glass spacer for a magnetic recording / reproducing device, and a magnetic recording / reproducing device. [Background technology]

[0002] Aluminum alloy substrates have been used as substrates for magnetic recording media such as hard disks (magnetic recording media substrates). However, it has been pointed out that aluminum alloy substrates are prone to deformation and have insufficient smoothness of the substrate surface after polishing. For this reason, glass magnetic recording media substrates are now widely used (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-64921 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the process of forming a magnetic recording layer on a magnetic recording medium substrate, the film is usually formed at a high temperature, or a heat treatment is performed at a high temperature after the film is formed. Therefore, the glass for the magnetic recording medium substrate is required to have high heat resistance capable of withstanding the high-temperature treatment, specifically, to have a high glass transition temperature.

[0005] Furthermore, as magnetic recording media become thinner and their recording densities increase, there are growing demands for further reduction in warping and bending of the magnetic recording media during rotation of a spindle motor, and for the magnetic recording media to have sufficient strength for practical use. In order to meet these demands, it is desirable for the glass for use as a magnetic recording medium substrate to have high rigidity, specifically a high Young's modulus.

[0006] As described above, glass for use as a magnetic recording medium substrate is desired to have excellent heat resistance and rigidity.

[0007] Therefore, an object of one aspect of the present invention is to provide a glass for a magnetic recording medium substrate that is excellent in heat resistance and rigidity. [Means for solving the problem]

[0008] One aspect of the present invention is SiO 2 The content is 56 to 80 mol %, Li 2 O content is 1 to 10 mol %, B 2 O 3 The content is 0 to 4 mol%, The total content of MgO and CaO (MgO+CaO) is 9 to 40 mol%, and Specific gravity is 2.75g / cm 3 Hereinafter, a glass for magnetic recording medium substrates, which is an amorphous oxide glass having a glass transition temperature of 650° C. or higher and a Young's modulus of 90 GPa or higher (hereinafter also referred to as "glass A"), Regarding.

[0009] Another aspect of the present invention is SiO 2 The content is 56 to 80 mol %, Li 2 O content is 1 to 10 mol %, B 2 O 3 The content is 0 to 4 mol%, The total content of MgO and CaO (MgO+CaO) is 9 to 40 mol%, Al 2 O 3 SiO content 2 and ZrO 2 The molar ratio of the total content of (SiO 2 +ZrO 2 ) / Al 2 O 3 ) from 2 to 13, and A glass for magnetic recording medium substrates that is an amorphous oxide glass having a glass transition temperature of 650° C. or higher and a Young's modulus of 90 GPa or higher (hereinafter also referred to as “glass B”); Regarding.

[0010] Glass A and glass B have the above glass composition, and have high heat resistance with a glass transition temperature of 650° C. or higher and high rigidity with a Young's modulus of 90 GPa or higher. Effect of the Invention

[0011] According to one aspect of the present invention, it is possible to provide a glass for a magnetic recording medium substrate having excellent heat resistance and rigidity. According to another aspect, it is also possible to provide a magnetic recording medium substrate made of the above-mentioned glass for a magnetic recording medium substrate, and a magnetic recording medium including the substrate. According to yet another aspect, it is also possible to provide a glass spacer for a magnetic recording device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Glass for magnetic recording media substrates] Glasses A and B are glasses for magnetic recording medium substrates that have the above glass composition and are amorphous oxide glasses with a glass transition temperature of 650° C. or higher and a Young's modulus of 90 GPa or higher.

[0013] Glasses A and B are amorphous glasses and oxide glasses. Unlike crystallized glass, amorphous glass is glass that does not contain a crystalline phase and exhibits a glass transition phenomenon upon heating. Also, oxide glass is glass in which the main network-forming component of the glass is an oxide. Glasses A and B will be described in more detail below. Unless otherwise specified, the matters described apply to both glasses A and B.

[0014] <Glass composition> In the present invention and this specification, the glass composition is expressed as a glass composition based on oxides. Here, "glass composition based on oxides" refers to a glass composition obtained by converting the glass raw materials into oxides that are present in the glass after being completely decomposed during melting. Furthermore, unless otherwise specified, the glass composition is expressed on a molar basis (mol %, molar ratio). The glass composition of the present invention and this specification can be determined by a method such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). Quantitative analysis is performed for each element using ICP-AES. The analytical values ​​are then converted into oxide notation. The analytical values ​​obtained by ICP-AES may contain a measurement error of, for example, about ±5% of the analytical value. Therefore, the oxide notation values ​​converted from the analytical values ​​may also contain an error of about ±5%. In the present invention and this specification, the content of a component being 0% or not being contained or not being introduced means that the component is substantially not contained, and the content of the component is at or below the impurity level. At or below the impurity level means, for example, less than 0.01%.

[0015] The glass compositions of glasses A and B will be described below.

[0016] SiO 2 is a glass network forming component and has the function of improving glass stability. SiO 2 is a component that also contributes to improving chemical durability. SiO in glasses A and B 2 From the viewpoint of improving rigidity, the content is 80% or less, preferably 75% or less, more preferably 70% or less, even more preferably 66% or less, still more preferably 64% or less, even more preferably 63% or less, and still more preferably 62% or less. 2From the viewpoint of maintaining chemical durability, the content is 56% or more, preferably 57% or more, more preferably 58% or more, even more preferably 59% or more, and even more preferably 60% or more.

[0017] Al 2 O 3 is a glass network forming component and has the function of improving heat resistance. 2 O 3 Also has the function of improving chemical durability. 2 O 3 From the viewpoint of improving heat resistance and chemical durability, the Al content in glasses A and B is 2 O 3 The content of Al in glasses A and B is preferably 5% or more, more preferably 8% or more, even more preferably 10% or more, still more preferably 12% or more, and still more preferably 13% or more. 2 O 3 The content is preferably 20% or less, more preferably 18% or less, even more preferably 17% or less, even more preferably 16% or less, and even more preferably 15.5% or less.

[0018] In glasses A and B, SiO 2 and Al 2 O 3 The total content (SiO 2 +Al 2 O 3 From the viewpoint of maintaining chemical durability, the SiO content in glasses A and B is preferably 65% ​​or more, more preferably 67% or more, even more preferably 69% or more, still more preferably 70% or more, even more preferably 72% or more, and still more preferably 74% or more. 2 and Al 2 O 3 The total content (SiO 2 +Al2 O 3 ) is preferably 80% or less, more preferably 78% or less, even more preferably 77% or less, even more preferably 76% or less, and even more preferably 75% or less.

[0019] B 2 O 3 is a component that forms a glass network, reduces the specific gravity of the glass, and improves the melting property. 2 O 3 is easily volatilized during melting and tends to destabilize the glass component ratio. In addition, excessive incorporation of B tends to reduce chemical durability. 2 O 3 The content of is 0 to 4%. 2 O 3 The content of is preferably 3.00% or less, more preferably 2.00% or less, even more preferably 1.50% or less, even more preferably 1.00% or less, even more preferably 0.50% or less, and even more preferably 0.30% or less. 2 O 3 The content is preferably 0.00% or more, more preferably 0.05% or more, even more preferably 0.10% or more, and even more preferably 0.15% or more.

[0020] Among the alkaline earth metal oxides MgO, CaO, SrO, and BaO, MgO has the function of increasing the Young's modulus of glass, the function of increasing the thermal expansion coefficient, and the function of improving the meltability and moldability of glass. The specific elastic modulus will be described in detail later. In one embodiment, MgO is an essential component. From the viewpoint of obtaining the above functions well, the content of MgO in glasses A and B is preferably 3% or more, more preferably 5% or more, even more preferably 7% or more, even more preferably 8% or more, and even more preferably 9% or more. In addition, from the viewpoint of maintaining glass stability, the content of MgO in glasses A and B is preferably 28% or less, more preferably 25% or less, even more preferably 22% or less, even more preferably 20% or less, even more preferably 18% or less, even more preferably 16% or less, even more preferably 15% or less, and even more preferably 14% or less.

[0021] The CaO content in glasses A and B is 0% or more. CaO also has the function of increasing the Young's modulus and specific elastic modulus of glass, the function of increasing the thermal expansion coefficient, and the function of improving the meltability and moldability of glass. From the viewpoint of obtaining these functions well, the CaO content in glasses A and B is preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, and even more preferably 5% or more. In addition, from the viewpoint of maintaining chemical durability, the CaO content in glasses A and B is preferably 18% or less, more preferably 15% or less, even more preferably 12% or less, even more preferably 10% or less, even more preferably 8% or less, and even more preferably 7% or less.

[0022] From the viewpoint of improving rigidity, the total content of MgO and CaO (MgO+CaO) in glasses A and B is 9% or more, preferably 11% or more, more preferably 13% or more, even more preferably 15% or more, even more preferably 16% or more, and even more preferably 17% or more. From the viewpoint of glass stability, the total content of MgO and CaO (MgO+CaO) in glasses A and B is 40% or less, preferably 35% or less, more preferably 30% or less, even more preferably 27% or less, even more preferably 25% or less, even more preferably 23% or less, even more preferably 21% or less, and even more preferably 20% or less.

[0023] The molar ratio of the CaO content to the MgO content (CaO / MgO) in glasses A and B is preferably 2.5 or less, more preferably 2.3 or less, even more preferably 2.1 or less, even more preferably 1.9 or less, even more preferably 1.6 or less, even more preferably 1.4 or less, even more preferably 1.1 or less, and still more preferably 1.0 or less, from the viewpoint of increasing Young's modulus and specific elastic modulus and improving glass stability. The molar ratio (CaO / MgO) is 0 or more, and from the viewpoint of improving glass stability, it is preferably 0.05 or more, more preferably 0.100 or more, even more preferably 0.120 or more, and even more preferably 0.150 or more.

[0024] SrO improves the meltability, moldability, and glass stability of the glass, and increases the thermal expansion coefficient. From the viewpoints of maintaining chemical durability, reducing the specific gravity, and reducing raw material costs, the SrO content in Glasses A and B is preferably 0 to 2%. The SrO content is more preferably in the range of 0 to 1.5%, even more preferably in the range of 0 to 1%, and even more preferably in the range of 0 to 0.5%. In one embodiment, it is preferable that no SrO is contained, that is, the SrO content is 0%.

[0025] Both BaO and SrO are components that increase the specific gravity of the glass. From the viewpoint of reducing the specific gravity of the glass, the total content of BaO and SrO (BaO+SrO) in Glasses A and B is preferably 0 to 2%, more preferably 0 to 1.5%, even more preferably 0 to 1%, and even more preferably 0 to 0.5%. In one embodiment, it is preferable that Glasses A and B do not contain BaO and SrO, that is, the total content of BaO and SrO (BaO+SrO) is 0%.

[0026] BaO also improves the meltability, moldability, and glass stability of the glass, and increases the thermal expansion coefficient. From the viewpoints of maintaining chemical durability, reducing the specific gravity, and reducing the raw material cost, the BaO content in Glasses A and B is preferably 0 to 2%, more preferably 0 to 1.5%, even more preferably 0 to 1.0%, and even more preferably 0 to 0.5%. In one embodiment, it is preferable that no BaO is contained, that is, the BaO content is 0%.

[0027] The molar ratio of the BaO content to the total content of MgO, CaO, SrO and BaO (BaO / (MgO+CaO+SrO+BaO)) is preferably 0.1 or less, more preferably 0.08 or less, even more preferably 0.06 or less, even more preferably 0.04 or less, even more preferably 0.03 or less, even more preferably 0.02 or less, and even more preferably 0.01 or less, from the viewpoints of improving rigidity, lowering specific gravity, increasing specific elastic modulus and improving glass stability. In one embodiment, the molar ratio (BaO / (MgO+CaO+SrO+BaO)) is preferably 0.

[0028] The molar ratio of the MgO content to the total content of MgO, CaO, SrO and BaO (MgO / (MgO+CaO+SrO+BaO)) is preferably 1 or less, more preferably 0.8 or less, and even more preferably 0.75 or less, from the viewpoint of improving glass stability. Moreover, the molar ratio (MgO / (MgO+CaO+SrO+BaO)) is preferably 0.3 or more, more preferably 0.5 or more, even more preferably 0.6 or more, and even more preferably 0.65 or more, from the viewpoint of increasing Young's modulus and specific elastic modulus and improving glass stability.

[0029] The total content of alkaline earth metal oxides (MgO+CaO+SrO+BaO) in glasses A and B is preferably 9% or more, more preferably 11% or more, even more preferably 13% or more, even more preferably 14% or more, and even more preferably 16% or more, from the viewpoint of improving the meltability and stability of the glass. Also, from the viewpoint of the chemical durability of the glass, the total content of alkaline earth metal oxides (MgO+CaO+SrO+BaO) in glasses A and B is preferably 40% or less, more preferably 35% or less, even more preferably 30% or less, even more preferably 28% or less, even more preferably 25% or less, even more preferably 22% or less, even more preferably 21% or less, and even more preferably 20% or less.

[0030] Among alkaline earth metal oxides, MgO has the function of increasing the Young's modulus and specific elastic modulus of glass, and is also a component that contributes to suppressing an increase in specific gravity. Therefore, MgO is a very useful component for increasing the Young's modulus, the specific elastic modulus, and the specific gravity of glass, and is particularly effective for increasing the Young's modulus and the specific gravity. CaO also has the function of increasing the Young's modulus and specific elastic modulus of glass, and is also a component that contributes to suppressing an increase in specific gravity, and is also an effective component for increasing the thermal expansion coefficient of glass. On the other hand, SrO and BaO increase the specific gravity and the raw material cost. From the above viewpoints, in glasses A and B, the molar ratio of the total content of MgO and CaO to the total content of MgO, CaO, SrO, and BaO {(MgO+CaO) / (MgO+CaO+SrO+BaO)} is preferably 0.7 to 1. The lower limit of the above molar ratio is more preferably 0.750 or more, even more preferably 0.800 or more, even more preferably 0.850 or more, even more preferably 0.900 or more, even more preferably 0.925 or more, even more preferably 0.950 or more, even more preferably 0.975 or more, and even more preferably 0.980 or more.

[0031] Li 2 Among the alkali metal oxides, O has a strong effect of improving the melting property and moldability of glass, and is also a suitable component for increasing the Young's modulus and imparting suitable rigidity to the magnetic recording medium substrate. 2 O is also a component that plays a role in lowering resistivity. More details on resistivity will be given later. 2 O is also a component that increases the thermal expansion coefficient. In addition, when glasses A and B are used as glasses for chemical strengthening, O is also a component that plays a role in ion exchange during chemical strengthening. On the other hand, Li 2 O is also a component that lowers the glass transition temperature. 2 The O content is 1 to 10%. 2The lower limit of the O content is preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, and even more preferably 4.2% or more. 2 The upper limit of the O content is preferably 8% or less, more preferably 7% or less, even more preferably 6% or less, and even more preferably 5% or less.

[0032] Li relative to the total content of MgO and CaO 2 Molar ratio of O content (Li 2 From the viewpoint of suppressing a decrease in the glass transition temperature, the molar ratio (LiO / (MgO+CaO)) is preferably 0.4 or less, more preferably 0.37 or less, even more preferably 0.35 or less, even more preferably 0.32 or less, and even more preferably 0.30 or less. 2 From the viewpoints of improving the meltability of the glass, suppressing the generation of bubbles, and reducing the specific resistance, the ratio of MgO to CaO is preferably 0.03 or more, more preferably 0.05 or more, even more preferably 0.08 or more, still more preferably 0.10 or more, even more preferably 0.15 or more, even more preferably 0.20 or more, and still more preferably 0.21 or more.

[0033] Na 2 O is a component that improves the meltability and formability of glass, increases the thermal expansion coefficient, and reduces the viscosity of glass during fining, accelerating bubble removal. In addition, when glasses A and B are used as glasses for chemical strengthening, O is also a component that is responsible for ion exchange during chemical strengthening. Taking the above functions into consideration, Na in glasses A and B is 2 The O content is preferably 0 to 10%, more preferably 0 to 8%, even more preferably 0 to 7%, still more preferably 0 to 6%, even more preferably 0 to 5%, even more preferably 0 to 3%, and even more preferably 0 to 1%.

[0034] Li2 Na vs. O content 2 Molar ratio of O content (Na 2 O / Li 2 From the viewpoint of improving rigidity, the molar ratio (Na O) is preferably 5 or less, more preferably 3 or less, even more preferably 2 or less, even more preferably 1 or less, and even more preferably 0.5 or less. 2 O / Li 2 O) can be 0.

[0035] K 2 O also works to improve the meltability and formability of the glass, and is also a component that increases the thermal expansion coefficient. On the other hand, if incorporated in excess, it tends to reduce chemical durability, especially acid resistance, and when used as a glass substrate, it increases alkali elution from the substrate surface, and the precipitated alkali may affect the film properties of the magnetic recording layer, etc. Taking the above points into consideration, the K content in glasses A and B was 2 The content of O is preferably 0 to 5%, more preferably 0 to 3%, further preferably 0 to 2%, and even more preferably 0 to 1%. 2 It is preferable that it does not contain O.

[0036] Li 2 O content, Na 2 O content and K content 2 Regarding the O content, from the viewpoint of improving the melting property of the glass, 4×Li 2 O content, 2×Na 2 O content and K content 2 Sum of O content (4Li 2 O+2Na 2 O+K 2 O) is preferably 8% or more. 2 O+2Na 2 O+K 2O) is preferably 8% or more in terms of reducing the resistivity. From the above viewpoints, the above sum is more preferably 10% or more, even more preferably 12% or more, even more preferably 14% or more, even more preferably 16% or more, even more preferably 17% or more, even more preferably 17.3% or more, even more preferably 17.5% or more, and even more preferably 17.8% or more. Also, from the viewpoint of increasing the glass transition temperature, 4×Li 2 O content, 2×Na 2 O content and K content 2 Sum of O content (4Li 2 O+2Na 2 O+K 2 O) is preferably 27% or less, more preferably 25% or less, even more preferably 23% or less, even more preferably 21% or less, even more preferably 20% or less, and even more preferably 19% or less.

[0037] Li 2 O, Na 2 O and K 2 SiO relative to the total O content 2 Molar ratio of content (SiO 2 / (Li 2 O+Na 2 O+K 2 From the viewpoint of increasing the glass transition temperature, the molar ratio (SiO 2 / (Li 2 O+Na 2 O+K 2 O)) is preferably 22 or less, more preferably 20 or less, even more preferably 17 or less, still more preferably 15 or less, and still more preferably 14 or less, from the viewpoint of improving the meltability and rigidity of the glass.

[0038] Li 2 O, Na2 O and K 2 Li relative to the total O content 2 Molar ratio of O content (Li 2 O / (Li 2 O+Na 2 O+K 2 From the viewpoints of increasing the Young's modulus and specific elastic modulus, improving the solubility, and decreasing the specific resistance, the molar ratio (Li) is preferably 0.10 or more, more preferably 0.30 or more, even more preferably 0.50 or more, even more preferably 0.70 or more, even more preferably 0.80 or more, even more preferably 0.90 or more, and even more preferably 0.95 or more. In one embodiment, the molar ratio (Li 2 O / (Li 2 O+Na 2 O+K 2 O) can be 1.

[0039] Li 2 O, Na 2 O and K 2 Na content relative to total O content 2 Molar ratio of O content (Na 2 O / (Li 2 O+Na 2 O+K 2 O)) can be 0 or more, and from the viewpoint of suppressing a decrease in Young's modulus and specific elastic modulus, is preferably 5 or less, more preferably 2 or less, still more preferably 1 or less, even more preferably 0.8 or less, and still more preferably 0.5 or less.

[0040] 5×Li 2 O content, 3×Na 2 O content, 3×K 2 O content, 2×B 2 O 3 content, MgO content, 2×CaO content, 3×SrO content and BaO content (5Li 2 O+3Na 2 O+3K 2 O+2B 2 O 3From the viewpoint of increasing the thermal expansion coefficient, the sum (5Li+MgO+2CaO+3SrO+BaO) is preferably 32% or more, more preferably 35% or more, even more preferably 38% or more, even more preferably 40% or more, even more preferably 42% or more, and even more preferably 44% or more. 2 O+3Na 2 O+3K 2 O+2B 2 O 3 +MgO+2CaO+3SrO+BaO) is preferably 58% or less, more preferably 56% or less, even more preferably 54% or less, still more preferably 52% or less, even more preferably 51% or less, and even more preferably 50% or less.

[0041] MgO and Li 2 CaO and Na relative to the total O content 2 Molar ratio of the total content of O ((CaO + Na 2 O) / (MgO+Li 2 From the viewpoint of improving the glass stability, the molar ratio ((CaO+Na 2 O) / (MgO+Li 2 From the viewpoint of suppressing a decrease in Young's modulus and specific elastic modulus, O) is preferably 2.5 or less, more preferably 2 or less, even more preferably 1.5 or less, even more preferably 1.0 or less, even more preferably 0.8 or less, and even more preferably 0.6 or less.

[0042] Li 2 O, Na 2 O and K 2O is a component that improves the meltability and moldability of the glass and increases the thermal expansion coefficient. From the viewpoint of obtaining the functions of these components well, the total content of alkali metal oxides in Glasses A and B (Li 2 O+Na 2 O+K 2 O) is preferably 2.5% or more, more preferably 3% or more, even more preferably 3.5% or more, and even more preferably 4% or more. On the other hand, from the viewpoint of maintaining the heat resistance and chemical durability of the glass, the total content of alkali metal oxides (Li 2 O+Na 2 O+K 2 O) is preferably 10% or less, more preferably 8% or less, even more preferably 7% or less, even more preferably 6% or less, and even more preferably 5% or less. When the glass contains two or more kinds of alkali metal oxides, a mixed alkali effect can be obtained, which reduces or prevents the elution of alkali from the glass surface.

[0043] TiO 2 Although TiO has the function of improving glass stability and chemical durability as well as improving rigidity, its incorporation in an excessive amount can raise the liquidus temperature of the glass, leading to deterioration of devitrification resistance and an increase in specific gravity. 2 The content is preferably 0 to 10%, more preferably 0 to 8%, even more preferably 0 to 6%, still more preferably 0 to 4%, even more preferably 0 to 3%, even more preferably 0 to 2%, and still more preferably 0 to 1%.

[0044] TiO relative to the total content of MgO and CaO 2 and Al 2 O 3 The molar ratio of the total content of (TiO 2 +Al 2 O 3From the viewpoints of suppressing the generation of bubbles, improving chemical durability, and increasing the hardness of the glass, the molar ratio ((TiO 2 +Al 2 O 3 From the viewpoints of improving glass stability, increasing the specific elastic modulus, and decreasing the specific gravity, the ratio (MgO+CaO)) is preferably 2 or less, more preferably 1.800 or less, even more preferably 1.600 or less, still more preferably 1.400, even more preferably 1.200 or less, and still more preferably 1.000 or less.

[0045] ZrO 2 ZrO has the function of improving chemical durability and also the function of improving rigidity. However, excessive incorporation of ZrO may reduce the melting property of the glass and may cause the raw materials to remain unmelted. Therefore, ZrO in Glasses A and B is 2 The content of ZrO is preferably 0 to 5%, more preferably 0 to 3%, further preferably 0 to 2%, even more preferably 0 to 1%, and still more preferably 0 to 0.5%. 2 The content can be 0.00%.

[0046] MgO content, 0.7×CaO content, Li 2 O content, TiO 2 Content and ZrO 2 Sum of contents (MgO+0.7CaO+Li 2 O+TiO 2 +ZrO 2 From the viewpoint of increasing the specific elastic modulus, the sum (MgO+0.7CaO+Li 2 O+TiO 2+ZrO 2 ) is preferably 40% or less, more preferably 35% or less, even more preferably 30% or less, still more preferably 28% or less, and even more preferably 25% or less, from the viewpoint of suppressing a decrease in glass stability and a decrease in glass transition temperature.

[0047] Al 2 O 3 SiO content 2 and ZrO 2 The molar ratio of the total content of (SiO 2 +ZrO 2 ) / Al 2 O 3 From the viewpoint of improving chemical durability, in glass B, the molar ratio ((SiO 2 +ZrO 2 ) / Al 2 O 3 From the viewpoints of improving rigidity and increasing the specific elastic modulus, in glass B, Al is 13 or less, preferably 10 or less, more preferably 9 or less, even more preferably 8 or less, still more preferably 7 or less, and even more preferably 6 or less. 2 O 3 SiO content 2 and ZrO 2 The molar ratio of the total content of (SiO 2 +ZrO 2 ) / Al 2 O 3 From the viewpoint of improving chemical durability, Al is preferably 2 or more, and from the viewpoint of improving rigidity and achieving a high specific elastic modulus, Al is preferably 13 or less. 2 O 3 SiO content 2 and ZrO 2 The molar ratio of the total content of (SiO 2 +ZrO 2 ) / Al 2 O 3For more preferred ranges of (a), see the above description regarding glass B.

[0048] ZnO has the function of improving meltability and rigidity, but excessive incorporation raises the liquidus temperature. From the above viewpoints, the ZnO content in glasses A and B is preferably 0 to 5%, more preferably 0 to 3%, further preferably 0 to 2%, even more preferably 0 to 1%, and still more preferably 0 to 0.5%. In one embodiment, the ZnO content can be 0.00%.

[0049] P 2 O 5 Although P can be incorporated into glasses A and B, excessive incorporation tends to decrease the chemical durability. 2 O 5 The content of P is preferably 0 to 2%. 2 O 5 The content of P is more preferably 0 to 1%, and further preferably 0 to 0.5%. 2 O 5 The content can be 0.00%.

[0050] SiO 2 Content, Al 2 O 3 Content, B 2 O 3 Content, P 2 O 5 Content, 1.5×Na 2 O content, 1.5×K 2 The sum of the O content, 2×SrO content, 3×BaO content and ZnO content (SiO 2 +Al 2 O 3 +B 2 O 3 +P 2 O 5 +1.5Na 2 O+1.5K 2From the viewpoint of improving rigidity, the content of ZnO (O+2SrO+3BaO+ZnO) is preferably 86% or less, more preferably 84% or less, even more preferably 82% or less, still more preferably 80% or less, even more preferably 78% or less, and even more preferably 77% or less.

[0051] SiO 2 Content, Al 2 O 3 Content, B 2 O 3 Content, P 2 O 5 Content, Na 2 O content, K 2 The sum of the O content, CaO content, 2×SrO content, and 3×BaO content (SiO 2 +Al 2 O 3 +B 2 O 3 +P 2 O 5 +Na 2 O+K 2 From the viewpoint of achieving a high specific elastic modulus, the content of the SiO2+CaO+2SrO+3BaO) is preferably 92% or less, more preferably 90% or less, even more preferably 88% or less, even more preferably 86% or less, and even more preferably 85% or less.

[0052] B 2 O 3 , SiO 2 , Al 2 O 3 and P 2 O 5 P relative to the total content of 2 O 5 Molar ratio of content (P 2 O 5 / (B 2 O 3 +SiO 2 +Al 2 O 3 +P 2 O 5From the viewpoints of improving glass stability, improving rigidity, increasing the specific elastic modulus, and improving chemical durability, the molar ratio (P) is preferably 0.005 or less, more preferably 0.003 or less, even more preferably 0.002 or less, and even more preferably 0.001 or less. 2 O 5 / (B 2 O 3 +SiO 2 +Al 2 O 3 +P 2 O 5 )) can be 0.

[0053] Glasses A and B contain SnO 2 , CEO 2 and Sb 2 O 3 In one embodiment, the composition may include one or more selected from the group consisting of SnO 2 and CeO 2 In another embodiment, the total content of glasses A and B is 0%. 2 and / or CeO 2 and SnO 2 and CeO 2 The total content of SnO 2 +CeO 2 ) is preferably 0.05 to 2%. 2 and CeO 2 By making the total content of SnO 0.05% or more, a sufficient fining effect can be obtained, and residual bubbles can be reduced or suppressed. 2 +CeO 2 By keeping the total content (SnO 2 +CeO 2The lower limit of the total content (SnO 2 +CeO 2 The upper limit of ) is preferably 1.5% or less, more preferably 1.2% or less, even more preferably 1.0% or less, still more preferably 0.70% or less, even more preferably 0.65% or less, even more preferably 0.60% or less, even more preferably 0.55% or less, and even more preferably 0.50% or less.

[0054] SnO 2 Sb has the effect of promoting fining when the melting temperature of glass is relatively high (temperature range of about 1400 to 1600°C). 2 O 3 In order to remove bubbles from glasses with high melting temperatures, in one embodiment, glasses A and B contain SnO 2 It is preferable to incorporate SnO 2 From the viewpoint of obtaining a clarification effect, the content of SnO is preferably 0.01% or more, more preferably 0.05% or more, even more preferably 0.10% or more, even more preferably 0.15% or more, and even more preferably 0.20% or more. 2 The content is preferably 2% or less, more preferably 1.5% or less, even more preferably 1.0% or less, even more preferably 0.8% or less, and even more preferably 0.5% or less.

[0055] CEO 2 SnO 2 It is a component that has a fining effect on glass, just like CeO 2has the function of taking in oxygen and fixing it as a glass component when the melting temperature of the glass is relatively low (temperature range of about 1200 to 1400 °C), so in one embodiment, CeO is added to glasses A and B as a fining agent. 2 It is preferable to introduce CeO 2 From the viewpoint of obtaining a clarification effect, the content of CeO is preferably 0.01% or more, more preferably 0.05% or more, even more preferably 0.08% or more, and even more preferably 0.10% or more. 2 The content of SnO is preferably 2% or less, more preferably 1.5% or less, even more preferably 1.0% or less, even more preferably 0.8% or less, even more preferably 0.5% or less, and even more preferably 0.3% or less. 2 and CeO 2 By coexisting SnO, a fining effect can be obtained in a wide temperature range. 2 and CeO 2 It is preferable to include both.

[0056] Sb 2 O 3 From the viewpoint of reducing the environmental impact, it is desirable to refrain from using Sb in glasses A and B. 2 O 3 The content of Sb is preferably in the range of 0 to 0.5%. 2 O 3 The content of Sb is preferably 0.3% or less, more preferably 0.1% or less, even more preferably 0.05% or less, and even more preferably 0.02% or less. 2 O 3 It is particularly preferred that it does not contain

[0057] CEO 2 If included, CeO 2 SnO content 2 Molar ratio of content (SnO 2 / CeO 2) can be 0 or more, preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, even more preferably 0.7 or more, even more preferably 0.9 or more, even more preferably 1.0 or more, even more preferably 1.2 or more, and even more preferably 1.4 or more. In addition, the molar ratio (SnO 2 / CeO 2 ) is preferably 7 or less, more preferably 6 or less, even more preferably 5 or less, even more preferably 4 or less, even more preferably 3.5 or less, even more preferably 3.0 or less, even more preferably 2.5 or less, even more preferably 2.3 or less, even even more preferably 2.1 or less, 1.9 or less, 1.8 or less, or 1.7 or less. As will be described later with respect to resistivity, in a mode in which electrical heating is performed during glass melting, a glass with low resistivity is preferred. Glass with low resistivity can be melted by lowering the temperature in the furnace during electrical heating. Lowering the temperature in the furnace increases the amount of SnO 2 Compared with CeO, which can exert a better fining effect at low temperatures, 2 Content of SnO 2 In other words, the molar ratio (SnO 2 / CeO 2 ) is preferably small.

[0058] The Fe content of glasses A and B is expressed as Fe in the oxide-based glass composition expressed by mass. 2 O 3In terms of the total amount of Fe, the content of Fe in the glass A and B may be 1% by mass or less, 0.7% by mass or less, 0.5% by mass or less, 0.4% by mass or less, 0.3% by mass or less, 0.1% by mass or less, 0.07% by mass or less, 0.05% by mass or less, 0.04% by mass or less, or 0.03% by mass or less. In one embodiment, the glass A and B may not contain Fe (the content is 0% by mass). The glass A and B may also contain one or more elements selected from the group consisting of Cu, Co, Yb, Mn, Nd, Pr, Nb, V, Cr, Ni, Mo, Ho, and Er.

[0059] Since Pb, Cd and As are substances that have a negative impact on the environment, it is preferable to avoid introducing these.

[0060] Glasses A and B can be produced by weighing, mixing, and thoroughly mixing glass raw materials such as oxides, carbonates, nitrates, sulfates, and hydroxides so as to obtain a desired glass composition, and then heating and melting the mixture in a melting vessel at, for example, a temperature range of 1400 to 1600°C, fining, stirring, and forming a homogenized molten glass that has been sufficiently bubble-free. For example, it is preferable to heat and melt the glass raw materials in a melting vessel at 1400 to 1550°C, and then raise the temperature of the obtained molten glass in a fining vessel and hold it at 1450 to 1600°C, and then lower the temperature to 1200 to 1400°C to allow the glass to flow and be formed. The glass may be heated by electrical heating, or may be heated by a heating method other than electrical heating.

[0061] <Glass properties> Glasses A and B can have the various glass physical properties described below by adjusting the compositions as described above.

[0062] (glass transition temperature) As described above, the magnetic recording medium substrate is usually subjected to high-temperature treatment in the process of forming a magnetic recording layer on the substrate. For example, in order to form a magnetic recording layer containing a magnetic material with high magnetic anisotropic energy, which has been developed in recent years for high-density recording of magnetic recording media, film formation is generally performed at high temperatures, or heat treatment is performed at high temperatures after film formation. If the magnetic recording medium substrate does not have heat resistance capable of withstanding such high-temperature treatment, the substrate will be exposed to high temperatures in the high-temperature treatment and the flatness of the substrate will be impaired. In contrast, glasses A and B have a glass transition temperature (hereinafter also referred to as "Tg"), which is an index of heat resistance, of 650°C or higher. If the substrate is made of glass having high heat resistance with a glass transition temperature of 650°C or higher, it can maintain excellent flatness even after high-temperature treatment. However, glasses A and B are not limited to glass for substrates of magnetic recording media having a magnetic recording layer containing a magnetic material that requires high-temperature treatment, and can be used to manufacture magnetic recording media equipped with various magnetic materials. The glass transition temperature is preferably 660° C. or higher, more preferably 670° C. or higher, even more preferably 675° C. or higher, even more preferably 680° C. or higher, even more preferably 685° C. or higher, and even more preferably 687° C. or higher. The upper limit of the glass transition temperature is, for example, about 770° C. or about 750° C., but is not particularly limited because a higher glass transition temperature is more preferable from the viewpoint of heat resistance.

[0063] (Young's Modulus) In order to meet the demand for improving the rigidity of the magnetic recording medium described above, it is desirable that the glass for the magnetic recording medium substrate has high rigidity. In this regard, the glasses A and B have a Young's modulus, which is an index of rigidity, of 90 GPa or more. The glass for the magnetic recording medium substrate having high rigidity and showing a Young's modulus of 90 GPa or more can suppress the substrate deformation during the rotation of the spindle motor, and therefore can suppress the warping and bending of the magnetic recording medium caused by the substrate deformation. The Young's modulus of the glasses A and B is preferably 91 GPa or more, more preferably 92 GPa or more, even more preferably 93 GPa or more, even more preferably 94 GPa or more, and even more preferably 95 GPa or more. The upper limit of the Young's modulus is, for example, about 120 GPa, but is not particularly limited because the higher the Young's modulus, the higher the rigidity is, and therefore, is preferable.

[0064] (specific gravity) The specific gravity of glass A is 2.75 or less. The specific gravity of glass B is preferably 2.75 or less. For glasses A and B, the specific gravity is more preferably 2.73 or less, even more preferably 2.70 or less, even more preferably 2.68 or less, even more preferably 2.64 or less, even more preferably 2.62 or less, and even more preferably 2.60 or less. By reducing the specific gravity of the glass for magnetic recording medium substrate, the magnetic recording medium substrate can be made lighter, and further the magnetic recording medium can be made lighter, which makes it possible to reduce the power consumption of the magnetic recording and reproducing device (generally called HDD (hard disk drive)). The lower limit of the specific gravity is, for example, about 2.40, but is not particularly limited because the lower the specific gravity, the more preferable it is.

[0065] (Specific elastic modulus) The specific elastic modulus is the Young's modulus of the glass divided by its density, where density is the specific gravity of the glass multiplied by the unit of g / cm 3From the viewpoint of providing a substrate that is less likely to deform, the specific elastic modulus of glasses A and B is preferably 30 MNm / kg or more, more preferably 32 MNm / kg or more, even more preferably 33 MNm / kg or more, even more preferably 34 MNm / kg or more, and even more preferably 35 MNm / kg or more. The upper limit of the specific elastic modulus is, for example, about 40 MNm / kg, but is not particularly limited since the higher the specific elastic modulus, the more preferable it is.

[0066] (Thermal expansion coefficient) A HDD incorporating a magnetic recording medium is structured so that the center part is held down by the spindle and clamp of a spindle motor to rotate the magnetic recording medium itself. Therefore, if there is a large difference in the thermal expansion coefficient of the magnetic recording medium substrate and the spindle material that constitutes the spindle part, there will be a mismatch between the thermal expansion and contraction of the spindle and the magnetic recording medium substrate in response to changes in the ambient temperature during use, resulting in deformation of the magnetic recording medium. If this phenomenon occurs, the head will not be able to read the written information, which will cause a decrease in the reliability of recording and playback. Therefore, it is desirable for the glass for the magnetic recording medium substrate to have a moderate thermal expansion coefficient similar to that of the spindle material (e.g., stainless steel, etc.). In general, the spindle material of an HDD has a thermal expansion coefficient of 70×10 -7 / °C or more, and the average linear expansion coefficient (thermal expansion coefficient) of the glass for magnetic recording medium substrates at 100 to 300°C is 40×10 -7 / °C or more, the difference in thermal expansion coefficient with the spindle material is small, which can contribute to improving the reliability of the magnetic recording medium. The average linear expansion coefficient (hereinafter also referred to as "α") of glasses A and B at 100 to 300°C is 40×10 -7 / °C or more, and 41×10 -7 / °C or more, and more preferably 42×10 -7 / °C or more, and more preferably 43×10 -7 / °C or more, and more preferably 44×10 -7 / °C or more, and more preferably 45×10 -7 / °C or more. The average linear expansion coefficient (α) of glasses A and B at 100 to 300°C is preferably 70×10 -7 / ℃ or less, and 68×10 -7 / °C or less, and more preferably 65×10 -7 / °C or less, more preferably 63×10 -7 / °C or less, and more preferably 60×10 -7 / °C or less, and more preferably 57×10 -7 / °C or less, and even more preferably 55×10 -7 / °C or less, and more preferably 53×10 -7 It is even more preferable that the temperature is 50×10 -7 / °C or less. In one embodiment, the average linear expansion coefficient (α) of glasses A and B at 100 to 300°C is 48×10 -7 / °C can be less than 47 x 10 -7 / °C or less.

[0067] (Glass Stability) Glasses A and B can exhibit high glass stability. Examples of methods for evaluating glass stability include a 1300°C 16-hour retention test and a 1250°C 16-hour retention test, which will be described in detail below. The evaluation result in the 1300°C 16-hour retention test is preferably A, more preferably the evaluation result in the 1300°C 16-hour retention test is A and the evaluation result in the 1250°C 16-hour retention test is A or B, and even more preferably the evaluation result in both retention tests is A.

[0068] (foam density) Glasses A and B can also reduce bubbles by adjusting the composition as described above. It is desirable to reduce bubbles in glass for magnetic recording medium substrates. This is for the following reasons. With the recent progress in high density recording, it is desirable to narrow the distance (called "flying height") between the head (magnetic head) for writing and reading data and the surface of the magnetic recording medium. However, if there are irregularities due to bubbles on the surface of the glass substrate for the magnetic recording medium, these irregularities are reflected on the surface of the magnetic recording medium, and the surface smoothness of the magnetic recording medium is reduced. If a magnetic head is brought close to the surface of a magnetic recording medium with poor surface smoothness, the magnetic head may come into contact with the surface of the magnetic recording medium and be damaged, so a certain flying height must be secured to prevent contact. From the above points, it is desirable to reduce bubbles in glass for magnetic recording medium substrates in order to narrow the flying height and to produce a magnetic recording medium with high surface smoothness. Regarding bubbles in the glass, the density of bubbles per unit mass, as the density of bubbles having a diameter of more than 0.03 mm as observed with an optical microscope (magnification 40 to 100 times), is preferably less than 50 bubbles / kg, more preferably less than 20 bubbles / kg, even more preferably less than 10 bubbles / kg, even more preferably 2 bubbles / kg or less, and most preferably 0 bubbles / kg.

[0069] (specific resistance) The resistivity of glasses A and B can be reduced by adjusting the composition as described above. Glasses with low resistivity are preferable in that they are less likely to corrode a melting furnace (e.g., made of bricks) or cause little corrode in the glass melting mode in which electrical heating is performed during glass melting. When electricity flows into the melting furnace during electrical heating, the melting furnace is corroded, but if the resistivity of the glass in the furnace is high, electricity flows easily through the melting furnace. When the melting furnace is corroded, glass may leak from the melting furnace, or components produced by the corrosion of the melting furnace may be mixed into the glass. Therefore, it is preferable to be able to suppress the corrosion of the melting furnace. As an index of low resistivity, the natural logarithm lnρ of the resistivity ρ may be adopted. In one embodiment, the natural logarithm lnρ (unitless) of the resistivity ρ (unit: Ω cm) at 1450° C. of Glasses A and B is preferably 3.20 or less, more preferably 3.00 or less, even more preferably 2.90 or less, still more preferably 2.80 or less, still more preferably 2.70 or less, still more preferably 2.68 or less, and still more preferably 2.65 or less. The natural logarithm lnρ of the resistivity ρ at 1450° C. can be, for example, 1 or more.

[0070] [Magnetic recording medium substrate] The magnetic recording medium substrate according to one embodiment of the present invention is made of Glass A or Glass B.

[0071] The magnetic recording medium substrate can be manufactured by heating glass raw materials to prepare a molten glass, forming the molten glass into a plate shape by any of the press molding, down-draw, and float methods, and processing the obtained plate-shaped glass. For example, in the press molding method, the molten glass flowing out of a glass flow pipe is cut into a predetermined volume to obtain a required molten glass lump, which is press molded in a press mold to produce a thin disk-shaped substrate blank. Next, a center hole is provided in the obtained substrate blank, and inner and outer periphery processing is performed, and both main surfaces are lapped and polished. Next, a cleaning process including acid cleaning and alkali cleaning is performed to obtain a disk-shaped substrate.

[0072] In one embodiment, the magnetic recording medium substrate has a homogeneous surface and internal composition. Here, the homogeneous surface and internal composition means that ion exchange has not been performed (i.e., the substrate does not have an ion exchange layer). For example, in cases where a HDD (hard disk drive) incorporating a magnetic recording medium is used in an environment where it is unlikely to be subjected to external shock, a magnetic recording medium substrate without an ion exchange layer can be used. Note that the magnetic recording medium substrate without an ion exchange layer is not subjected to an ion exchange process, and therefore the manufacturing cost can be significantly reduced.

[0073] In one embodiment, the magnetic recording medium substrate has an ion exchange layer on a part or the whole of the surface. Since the ion exchange layer exhibits compressive stress, the presence or absence of the ion exchange layer can be confirmed by breaking the substrate perpendicularly to the main surface and obtaining a stress profile on the fracture surface by the Babinet method. The "main surface" is the surface on which the magnetic recording layer of the substrate is provided or is provided. This surface is called the main surface because it is the surface with the largest area among the surfaces of the magnetic recording medium substrate, and in the case of a disk-shaped magnetic recording medium, it corresponds to the circular surface of the disk (excluding the central hole if there is one). The presence or absence of the ion exchange layer can also be confirmed by a method of measuring the concentration distribution of alkali metal ions in the depth direction from the substrate surface, etc.

[0074] The ion exchange layer can be formed by contacting an alkali salt with the substrate surface at high temperature and exchanging the alkali metal ions in the alkali salt with the alkali metal ions in the substrate. For ion exchange (also called "strengthening treatment" or "chemical strengthening"), known techniques can be applied, and for example, see paragraphs 0068 to 0069 of WO2011 / 019010A1.

[0075] The magnetic recording medium substrate has a thickness of, for example, 1.5 mm or less, preferably 1.2 mm or less, more preferably 1 mm or less, and the lower limit of the thickness is preferably 0.3 mm. The magnetic recording medium substrate is preferably in the shape of a disk having a center hole.

[0076] The magnetic recording medium substrate is made of amorphous glass, which can achieve superior surface smoothness when processed into a substrate compared to crystallized glass.

[0077] [Magnetic recording media] One aspect of the present invention relates to a magnetic recording medium having a magnetic recording layer on the above magnetic recording medium substrate.

[0078] Magnetic recording media are called magnetic disks, hard disks, etc., and are suitable for use in various magnetic recording and reproducing devices, such as internal storage devices (fixed disks, etc.) of desktop personal computers, server computers, notebook personal computers, mobile personal computers, etc., internal storage devices of portable recording and reproducing devices that record and replay images and / or sounds, recording and replay devices for car audio, etc. In the present invention and this specification, the term "magnetic recording and replay device" refers to a device that is capable of either or both of magnetically recording information and magnetically replaying information.

[0079] A magnetic recording medium has a configuration in which, for example, on the main surface of a magnetic recording medium substrate, at least an adhesive layer, an underlayer, a magnetic layer (magnetic recording layer), a protective layer, and a lubricant layer are laminated in that order from closest to the main surface. For example, the magnetic recording medium substrate is introduced into a film-forming apparatus that has been evacuated, and an adhesion layer through a magnetic layer are successively formed on the main surface of the magnetic recording medium substrate in an Ar atmosphere by DC (Direct Current) magnetron sputtering. For example, CrTi can be used as the adhesion layer, and for example, a material containing Ru or MgO can be used as the underlayer. Note that a soft magnetic layer and a heat sink layer may be added as appropriate. After the above film formation, C is deposited by, for example, CVD (Chemical Vapor Deposition). 2 H 4 A magnetic recording medium can be formed by forming a protective layer using the above-mentioned method and then performing a nitriding process to introduce nitrogen into the surface in the same chamber. After that, a lubricating layer can be formed by applying, for example, PFPE (polyfluoropolyether) onto the protective layer using a dip coating method.

[0080] For higher density recording of the magnetic recording medium, it is preferable that the magnetic recording layer contains a magnetic material with high magnetic anisotropy energy. From this point of view, a preferable magnetic material is an Fe-Pt magnetic material or a Co-Pt magnetic material. Here, "based" means containing. That is, the magnetic recording medium preferably has a magnetic recording layer containing Fe and Pt, or Co and Pt as the magnetic recording layer. For the magnetic recording layer containing such a magnetic material and the film formation method thereof, reference can be made to paragraph 0074 of WO2011 / 019010A1 and the description of the examples in the same publication. In addition, it is preferable that the magnetic recording medium having such a magnetic recording layer is applied to a magnetic recording device using a recording method called an energy-assisted recording method. Among the energy-assisted recording methods, a recording method in which magnetization reversal is assisted by irradiation of near-field light or the like is called a thermally assisted recording method, and a recording method in which magnetization reversal is assisted by microwaves is called a microwave-assisted recording method. For details of these, reference can be made to paragraph 0075 of WO2011 / 019010A1. As the magnetic material for forming the magnetic recording layer, a conventional CoPtCr-based material may be used.

[0081] In recent years, a DFH (Dynamic Flying Height) mechanism has been installed in a magnetic head to achieve a significant narrowing of the gap between the read / write element of the magnetic head and the surface of the magnetic recording medium (reducing the flying height), thereby achieving even higher recording density. The DFH mechanism is a function in which a heating unit such as a very small heater is provided near the read / write element of the magnetic head, and only the periphery of the element is protruded toward the surface of the medium. This reduces the distance (flying height) between the magnetic head and the magnetic recording layer of the medium, making it possible to pick up signals from smaller magnetic particles and achieve even higher recording density. However, on the other hand, the gap (flying height) between the element of the magnetic head and the surface of the medium becomes extremely small. If there are irregularities due to bubbles on the surface of the magnetic recording medium substrate, these irregularities are reflected on the surface of the magnetic recording medium, and the surface smoothness of the magnetic recording medium decreases. As described above, when a magnetic head is brought close to a surface of a magnetic recording medium with poor surface smoothness, the magnetic head may come into contact with the surface of the magnetic recording medium and be damaged, so that a certain flying height must be secured to prevent the contact. From the above points, it is desirable to reduce bubbles in the magnetic recording medium substrate in order to produce a magnetic recording medium with high surface smoothness. This is because reducing bubbles in the substrate makes it possible to narrow the flying height. Since the magnetic recording medium substrate preferably has reduced bubbles, the magnetic recording medium equipped with such a substrate is also suitable for a magnetic recording device equipped with a DFH mechanism with an extremely narrow flying height.

[0082] There is no particular limit to the dimensions of the magnetic recording medium substrate (e.g., magnetic disk substrate) and the magnetic recording medium (e.g., magnetic disk), but since high recording density is possible, it is also possible to miniaturize the medium and substrate. For example, the nominal diameter can be 2.5 inches, of course, but it can also be smaller (e.g., 1 inch, 1.8 inches), or 3 inches, 3.5 inches, etc. The plate thickness can be, for example, 0.3 to 2 mm, but glasses A and B are suitable for thin plate formation because of their excellent heat resistance and rigidity. By making the plate thinner, it is possible to increase the number of magnetic recording media that can be mounted on the HDD, thereby increasing the recording capacity of the HDD. From this viewpoint, the plate thickness is preferably set to a nominal value of 0.635 mm or less, more preferably 0.550 mm or less, even more preferably 0.500 mm or less, and even more preferably 0.400 mm or less.

[0083] [Glass spacer for magnetic recording / reproducing devices] One aspect of the present invention is SiO 2 The content is 56 to 80 mol %, Li 2 O content is 1 to 10 mol %, B 2 O 3 The content is 0 to 4 mol%, The total content of MgO and CaO (MgO+CaO) is 9 to 40 mol%, and Specific gravity is 2.75g / cm 3 A glass spacer for a magnetic recording / reproducing device, comprising an amorphous oxide glass having a glass transition temperature of 650° C. or higher and a Young's modulus of 90 GPa or higher, Regarding.

[0084] Another aspect of the present invention is SiO 2 The content is 56 to 80 mol %, Li 2 O content is 1 to 10 mol %, B 2 O 3 The content is 0 to 4 mol%, The total content of MgO and CaO (MgO+CaO) is 9 to 40 mol%, Al 2 O 3 SiO content 2 and ZrO 2 The molar ratio of the total content of (SiO 2 +ZrO 2 ) / Al 2 O 3 ) from 2 to 13, and a glass spacer for a magnetic recording / reproducing device, comprising an amorphous oxide glass having a glass transition temperature of 650° C. or higher and a Young's modulus of 90 GPa or higher; Regarding.

[0085] The magnetic recording medium can be used to magnetically record and / or reproduce information in a magnetic recording / reproducing device. The magnetic recording / reproducing device is usually provided with a spacer to fix the magnetic recording medium to the spindle of a spindle motor and / or to maintain a distance between a plurality of magnetic recording media. In recent years, it has been proposed to use a glass spacer as such a spacer. For reasons similar to those described above in detail for the glass for the magnetic recording medium substrate, it is desired that the glass spacer also has excellent heat resistance and rigidity. In contrast, the above glass can have excellent heat resistance and rigidity as described above in detail for glasses A and B, and is therefore suitable as a glass spacer for a magnetic recording / reproducing device.

[0086] The spacer for the magnetic recording and reproducing device is a ring-shaped member, and the details of the configuration, manufacturing method, etc. of the glass spacer are publicly known. For the manufacturing method of the glass spacer, the above description of the manufacturing method of the glass for a magnetic recording medium substrate and the manufacturing method of the magnetic recording medium substrate can be referred to. For other details such as the glass composition and glass properties of the glass spacer for the magnetic recording and reproducing device according to one aspect of the present invention, the above description of the glass for a magnetic recording medium substrate, the magnetic recording medium substrate, and the magnetic recording medium according to one aspect of the present invention can be referred to. The glass spacer for magnetic recording and reproducing devices may be made of the above-mentioned glass, or may have one or more films such as a conductive film provided on the surface of the above-mentioned glass. For example, in order to remove static electricity generated during rotation of the magnetic recording medium, a conductive film such as a NiP alloy may be formed on the surface of the glass spacer by plating, immersion, vapor deposition, sputtering, or other methods. The glass spacer may also be polished to increase its surface smoothness (for example, to an average surface roughness of 1 μm or less), which may increase the degree of adhesion between the magnetic recording medium and the spacer and suppress the occurrence of misalignment.

[0087] [Magnetic recording and playback device] One aspect of the present invention is A magnetic recording medium according to one embodiment of the present invention; and A glass spacer according to one aspect of the present invention; A magnetic recording and reproducing device including at least one of the above. Regarding.

[0088] A magnetic recording and reproducing device includes at least one magnetic recording medium and at least one spacer, and typically further includes a spindle motor for rotating the magnetic recording medium, and at least one magnetic head for recording and / or reproducing information on the magnetic recording medium. The magnetic recording and reproducing device according to an embodiment of the present invention may include the magnetic recording medium according to an embodiment of the present invention as at least one magnetic recording medium, or may include a plurality of the magnetic recording media according to an embodiment of the present invention. The magnetic recording and reproducing device according to an embodiment of the present invention may include the glass spacer according to an embodiment of the present invention as at least one spacer, or may include a plurality of the glass spacers according to an embodiment of the present invention. A small difference between the thermal expansion coefficient of the magnetic recording medium and the thermal expansion coefficient of the spacer is preferable from the viewpoint of suppressing the occurrence of phenomena that may occur due to the difference in the thermal expansion coefficients of the two, such as distortion of the magnetic recording medium and a decrease in stability during rotation due to misalignment of the magnetic recording medium. From this viewpoint, the magnetic recording and reproducing device according to an embodiment of the present invention preferably includes the magnetic recording medium according to an embodiment of the present invention as at least one magnetic recording medium, or as more magnetic recording media when multiple magnetic recording media are included, and includes the glass spacer according to an embodiment of the present invention as at least one spacer, or as more spacers when multiple spacers are included. For example, the magnetic recording and reproducing device according to an embodiment of the present invention may be one in which the glass constituting the magnetic recording medium substrate included in the magnetic recording medium and the glass constituting the glass spacer have the same glass composition.

[0089] The magnetic recording and reproducing device according to an embodiment of the present invention may include at least one of the magnetic recording medium according to an embodiment of the present invention and the glass spacer according to an embodiment of the present invention, and other aspects may be applied to known techniques related to magnetic recording and reproducing devices. In one embodiment, an energy-assisted magnetic recording head having an energy source (e.g., a heat source such as a laser light source, microwaves, etc.) for assisting magnetization reversal (assisting writing of a magnetic signal), a recording element portion, and a reproducing element portion can be used as the magnetic head. Such an energy-assisted recording magnetic recording and reproducing device including an energy-assisted magnetic recording head is useful as a magnetic recording and reproducing device having high recording density and high reliability. In addition, when manufacturing a magnetic recording medium used in an energy-assisted recording magnetic recording and reproducing device including a heat-assisted magnetic recording head having a laser light source or the like, a magnetic recording layer including a magnetic material with high magnetic anisotropic energy may be formed on a magnetic recording medium substrate. To form such a magnetic recording layer, a film is usually formed at a high temperature, or a heat treatment is performed at a high temperature after the film is formed. As a magnetic recording medium substrate that can have high heat resistance to such high temperature treatment, the magnetic recording medium substrate according to an embodiment of the present invention is preferable. However, the magnetic recording and reproducing device according to one aspect of the present invention is not limited to the energy-assisted magnetic recording and reproducing device. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments shown in the examples.

[0091] [Examples No. 1 to No. 76] Raw materials such as oxides, carbonates, nitrates, sulfates, and hydroxides were weighed and mixed to prepare a raw material blend so as to obtain glass having the composition shown in the table below. The raw materials blend was charged into a melting vat and heated and melted in the range of 1400-1600°C to obtain a molten glass. The molten glass was then held in a fining vat at 1400-1550°C for 6 hours, after which the temperature was lowered (cooled down) and held in the range of 1200-1400°C for 1 hour, after which the molten glass was shaped to obtain glass (amorphous oxide glass) for the following evaluations. The heating can be performed by various heating methods such as electrical heating.

[0092] [Evaluation method] (1) Glass transition temperature (Tg), average linear expansion coefficient (α) The glass transition temperature Tg and the average linear expansion coefficient α at 100 to 300° C. of each glass were measured using a thermomechanical analysis (TMA) device.

[0093] (2) Young’s modulus The Young's modulus of each glass was measured by an ultrasonic method.

[0094] (3) Specific gravity The specific gravity of each glass was measured by Archimedes' method.

[0095] (4) Specific elastic modulus The specific elastic modulus was calculated from the Young's modulus obtained in (2) above and the specific gravity obtained in (3).

[0096] (5) Glass stability 100 g of each glass was placed in a platinum crucible, which was then placed in a heating furnace with the temperature inside the furnace set to 1250°C or 1300°C, and left for 16 hours (holding test) while maintaining the furnace temperature. After 16 hours, the crucible was removed from the heating furnace, and the glass in the crucible was transferred onto a refractory material and cooled to room temperature. The presence or absence of crystals in each glass was observed under an optical microscope and evaluated according to the following criteria. A: No crystals were observed when observed under a magnified optical microscope (magnification 40 to 100 times). B: Crystals are observed when observed under a magnified optical microscope (magnification 40 to 100 times), but no crystals are observed by visual observation. C: Crystals are confirmed by visual observation.

[0097] (6) Foam density ranking A glass plate (substrate blank) with a thickness of about 1.2 mm was prepared from the molten glass obtained above. The surface of this glass plate was polished to be flat and smooth, and the inside of the glass was observed from the polished surface under an optical microscope at a magnification of 40 to 100 times, and the number of bubbles with a diameter of more than 0.03 mm (hereinafter simply referred to as "bubbles") was counted. The number of bubbles counted was divided by the mass of glass corresponding to the area observed under magnification to determine the bubble density. The bubble density rank was evaluated from rank S to rank F according to the bubble density obtained by the above method. Specifically, a bubble density of 0 bubbles / kg was ranked S, a bubble density of 2 bubbles / kg or less with bubbles present was ranked A, a bubble density of more than 2 bubbles / kg and less than 10 bubbles / kg was ranked B, a bubble density of 10 bubbles / kg or more and less than 20 bubbles / kg was ranked C, a bubble density of 20 bubbles / kg or more and less than 50 bubbles / kg was ranked D, a bubble density of 50 bubbles / kg or more and less than 80 bubbles was ranked E, and a bubble density of 80 bubbles / kg or more was ranked F.

[0098] (7) Natural logarithm lnρ of resistivity ρ(1450℃) The glass to be measured for resistivity was melted to prepare a molten glass at a temperature of t°C. The electrical conductivity σ (unit: S / cm) of this molten glass was measured using a Pt-Rh ring electrode (electrode distance 15 mm) at a voltage of 50 mV and a frequency of 20 kHz. The cell constant was measured using a standard solution with a concentration of 1 mol / dm 3 The electrical conductivity σ was determined for each temperature t at temperature intervals of about 25 to 45°C in the temperature range of about 1200°C to about 1600°C, and the electrical conductivity σ was determined for each temperature t at temperature intervals of about 25 to 45°C. The determined σ was plotted in an Arrhenius plot, and the σ at 1450°C was determined from the straight line. The resistivity ρ at 1450°C was determined from the σ at 1450°C thus determined by the formula resistivity ρ=1 / σ, and the natural logarithm lnρ of the determined ρ was calculated.

[0099] The results are shown in the table below.

[0100] [Table 1]

[0101] [Table 2]

[0102] [Table 3]

[0103] [Table 4]

[0104] [Table 5]

[0105] [Table 6]

[0106] [Table 7]

[0107] [Table 8]

[0108] [Table 9]

[0109] [Table 10]

[0110] From the results shown in the above table, it was confirmed that the glasses for magnetic recording medium substrates of the Examples all have excellent heat resistance and rigidity. Furthermore, it was also confirmed that the glasses for magnetic recording medium substrates of the Examples have low specific gravity and an appropriate thermal expansion coefficient. Regarding glass stability, in the retention test performed by the above method, the better the evaluation result at a lower temperature, the less likely the glass is to precipitate crystals in the molten state, and the lower the molding temperature can be used for molding. The lower the molding temperature, the longer the life of components of the molding device, such as the heating element, furnace body, and pipes. In particular, when a substrate blank is produced by press molding, the lower the molding temperature, the more preferable. Furthermore, if the molding temperature can be lowered, the glass viscosity can be increased for molding, and therefore volatilization, striae, and molding bubbles can be suppressed. Moreover, all of the glasses of the examples shown in the above table were ranked as S, A or B in bubble density, and it was confirmed that bubble generation was suppressed.

[0111] [Magnetic recording medium substrate fabrication] (1) Preparation of substrate blank Next, a disk-shaped substrate blank was produced by the following method A or B. Moreover, a glass blank for producing a glass spacer for a magnetic recording / reproducing device can be obtained by the same method. (Method A) The clarified and homogenized molten glass of the above-mentioned embodiment was flowed out at a constant flow rate from the flow pipe and received by a lower mold for press molding, and the flowed out molten glass was cut with a cutting blade so that a predetermined amount of molten glass gob was obtained on the lower mold. The lower mold on which the molten glass gob was placed was immediately removed from the bottom of the pipe, and the molten glass was press-molded into a thin disk shape with a diameter of 66 mm and a thickness of 1.2 mm using an upper mold and a body mold opposed to the lower mold. The press-molded product was cooled to a temperature at which it would not deform, and then removed from the mold and annealed to obtain a substrate blank. In the above-mentioned molding, the flowing molten glass was successively molded into a disk-shaped substrate blank using a plurality of lower molds. (Method B) The clarified and homogenized molten glass of the above-mentioned Example was continuously poured from above into a heat-resistant mold having a cylindrical through-hole, formed into a cylindrical shape, and removed from the bottom of the through-hole. After the removed glass was annealed, the glass was sliced ​​at regular intervals in a direction perpendicular to the cylindrical axis using a multi-wire saw to produce disk-shaped substrate blanks. Although the above-mentioned methods A and B were adopted in this embodiment, the following methods C and D are also suitable as methods for manufacturing a disk-shaped substrate blank. The following methods C and D are also suitable as methods for manufacturing a glass blank for producing a glass spacer for a magnetic recording / reproducing device. (Method C) The molten glass of the above-mentioned embodiment can be poured onto a float bath and formed into a sheet-like glass (formed by the float method), and then annealed, after which a disk-like glass can be hollowed out from the sheet glass to obtain a substrate blank. (Method D) The molten glass of the above-mentioned embodiment can be formed into a sheet-like glass by the overflow downdraw method (fusion method), annealed, and then a disk-like glass can be hollowed out from the sheet glass to obtain a substrate blank.

[0112] (2) Preparation of glass substrate A through hole was drilled in the center of the substrate blank obtained by each of the above methods, the outer and inner circumferences were ground, and the main surfaces of the disks were lapped and polished (mirror polished) to finish them into glass substrates for magnetic disks with a diameter of 65 mm and a thickness of 0.8 mm. Also, by using the same method, glass blanks for producing glass spacers for magnetic recording and reproducing devices can be finished into glass spacers for magnetic recording and reproducing devices. The glass substrate obtained above was treated with 1.7% by mass of hydrofluorosilicic acid (H 2 The substrate was washed with an aqueous solution of SiF, then with a 1% by mass aqueous solution of potassium hydroxide, and then rinsed with pure water and dried. When the surface of the substrate made from the glass of the example was observed under magnification, no surface roughness was observed, and the surface was smooth.

[0113] [Magnetic recording medium (magnetic disk) production] An adhesive layer, an underlayer, a magnetic recording layer, a protective layer and a lubricant layer were formed in this order on the main surface of a glass substrate obtained from the glass of the example by the following method, to obtain a magnetic disk.

[0114] First, using a deposition apparatus that had been evacuated, an adhesive layer, an underlayer, and a magnetic recording layer were successively deposited in an Ar atmosphere by DC magnetron sputtering.

[0115] At this time, the adhesion layer was formed using a CrTi target to be an amorphous CrTi layer with a thickness of 20 nm. Then, a 10 nm thick layer made of MgO was formed as an underlayer. The magnetic recording layer was formed using an FePtC or CoPtC target at a deposition temperature of 200 to 400°C to be a 10 nm thick granular layer of FePt or CoPt.

[0116] After the magnetic recording layer was formed, the magnetic disk was transferred from the deposition device to a heating furnace and annealed. The temperature in the heating furnace during annealing was set to a range of 500 to 700°C. 10 Magnetic particles of CoPt-based alloy or FePt-based alloy with an ordered structure are formed. 10 Heating may be applied so as to produce an ordered structure.

[0117] Next, a protective layer made of hydrogenated carbon was formed to a thickness of 3 nm by CVD using ethylene as the material gas. After this, a lubricating layer made of PFPE (perfluoropolyether) was formed by dip coating. The thickness of the lubricating layer was 1 nm. A magnetic disk was obtained through the above manufacturing process. The obtained magnetic disk was mounted in a hard disk drive equipped with a DFH mechanism, and magnetic signals were recorded and reproduced in the recording area on the main surface of the magnetic disk at a recording density of 1000 gigabits per square inch. No collision between the magnetic head and the magnetic disk surface (crash failure) was observed.

[0118] In addition, a glass spacer obtained by the above manufacturing process using the glass of the embodiment and having a conductive film of NiP alloy formed on its surface (glass spacer with NiP alloy film) was mounted in a hard disk drive equipped with a DFH mechanism, and magnetic signals were recorded and reproduced at a recording density of 1,000 gigabits per square inch in a recording area on the main surface of a magnetic disk separately prepared using a substrate made of a material different from the glass according to one embodiment of the present invention (glass A or glass B). No collision between the magnetic head and the magnetic disk surface (crash failure) was observed.

[0119] In addition, when the magnetic disk and the glass spacer with NiP alloy film manufactured above using the same glass material according to one embodiment of the present invention were mounted on a hard disk drive equipped with a DFH mechanism and magnetic signals were recorded and reproduced in the recording area on the main surface of the magnetic disk at a recording density of 1000 gigabits per square inch, no collision between the magnetic head and the magnetic disk surface (crash failure) was observed. Here, since the glass substrate and the glass spacer included in the magnetic disk are made of the same glass material, it is clear that the phenomenon that may occur due to the difference in thermal expansion coefficient described above does not occur.

[0120] According to one aspect of the present invention, it is possible to provide a magnetic recording medium suitable for high density recording.

[0121] Finally, the above-mentioned aspects will be summarized.

[0122] According to one aspect, SiO 2 Content is 56-80 mol%, Li 2 O content is 1 to 10 mol%, B 2 O 3 The content is 0-7 mol%, and the total content of MgO and CaO (MgO+CaO) is 9-40 mol%. and the specific gravity is 2.75g / cm 3 Glass for magnetic recording medium substrates, which is an amorphous oxide glass having a glass transition temperature of 650° C. or higher and a Young's modulus of 90 GPa or higher; and SiO 2 Content is 56-80 mol%, Li 2 O content is 1 to 10 mol%, B 2 O 3 The content is 0-4 mol%, the total content of MgO and CaO (MgO+CaO) is 9-40 mol%, and Al 2 O 3 SiO content 2 and ZrO 2 The molar ratio of the total content of (SiO 2 +ZrO 2 ) / Al 2 O 3 a glass for a magnetic recording medium substrate, which is an amorphous oxide glass having a glass transition temperature of 650° C. or higher and a Young's modulus of 90 GPa or higher, and is provided.

[0123] According to one aspect, SiO 2 Content is 56-80 mol%, Li 2 O content is 1 to 10 mol%, B 2 O 3 The content is 0-4 mol%, the total content of MgO and CaO (MgO+CaO) is 9-40 mol%, and the specific gravity is 2.75 g / cm 3 A glass spacer for a magnetic recording / reproducing device, comprising an amorphous oxide glass having a glass transition temperature of 650° C. or higher and a Young's modulus of 90 GPa or higher; and SiO 2 Content is 56-80 mol%, Li 2 O content is 1 to 10 mol%, B 2 O 3 The content is 0 to 7 mol%, the total content of MgO and CaO (MgO + CaO) is 9 to 40 mol%, and Al 2 O 3 SiO content 2 and ZrO 2 The molar ratio of the total content of (SiO 2 +ZrO 2 ) / Al 2 O 3a glass spacer for a magnetic recording / reproducing device, the glass spacer comprising an amorphous oxide glass having a glass transition temperature of 650° C. or higher and a Young's modulus of 90 GPa or higher, wherein the molecular weight of the amorphous oxide glass is 2 to 13; is provided.

[0124] The above-mentioned glass for a magnetic recording medium substrate is excellent in heat resistance and rigidity, as is the glass spacer for a magnetic recording / reproducing device.

[0125] In one embodiment, the average linear expansion coefficient of the oxide glass at 100 to 300° C. is 40×10 -7 ~70×10 -7 / °C range.

[0126] In one embodiment, the CaO content of the oxide glass can be in the range of 0 to 18 mol %.

[0127] In one embodiment, the total content of BaO and SrO in the oxide glass can be in the range of 0 to 2 mol %.

[0128] In one embodiment, the Li 2 O, Na 2 O and K 2 Total O content (Li 2 O+Na 2 O+K 2 O) can range from 2.5 to 10 mole %.

[0129] In one embodiment, the oxide glass is SnO 2 and CeO 2 The total content of SnO 2 +CeO 2 ) can be in the range of 0.05 to 2 mol %.

[0130] In one embodiment, the CeO of the oxide glass 2 SnO content 2 Molar ratio of content (SnO 2 / CeO 2 ) can be 1 or more.

[0131] In one embodiment, the oxide glass comprises, in mole percent, SiO 2 Content is 56-65%, Al 2 O 3 Content is 5-20%, B 2 O 3 Content is 0-4%, MgO content is 3-28%, Li 2 O content 1-10%, SiO 2 and Al 2 O 3 The total content (SiO 2 +Al 2 O 3 ) is 65-80%, the total content of MgO and CaO (MgO+CaO) is 11-30%, the total content of MgO, CaO, SrO and BaO (MgO+CaO+SrO+BaO) is 12-30%, MgO content, 0.7×CaO content, Li 2 O content, TiO 2 Content and ZrO 2 Sum of contents (MgO+0.7CaO+Li 2 O+TiO 2 +ZrO 2 ) is 16% or more, 5×Li 2 O content, 3×Na 2 O content, 3×K 2 O content, 2×B 2 O 3 content, MgO content, 2×CaO content, 3×SrO content and BaO content (5Li 2 O+3Na 2 O+3K 2 O+2B 2 O 3 +MgO+2CaO+3SrO+BaO) is 32~58%, SiO 2 Content, Al 2 O 3 Content, B 2 O 3 Content, P 2 O 5 Content, 1.5×Na 2 O content, 1.5×K 2 The sum of the O content, 2×SrO content, 3×BaO content and ZnO content (SiO 2 +Al 2 O3 +B 2 O 3 +P 2 O 5 +1.5Na 2 O+1.5K 2 O+2SrO+3BaO+ZnO) is 86% or less, SiO 2 Content, Al 2 O 3 Content, B 2 O 3 Content, P 2 O 5 Content, Na 2 O content, K 2 The sum of the O content, CaO content, 2×SrO content, and 3×BaO content (SiO 2 +Al 2 O 3 +B 2 O 3 +P 2 O 5 +Na 2 O+K 2 O+CaO+2SrO+3BaO) is 92% or less, the molar ratio of the CaO content to the MgO content (CaO / MgO) is 2.5 or less, Li 2 Na content relative to O content 2 Molar ratio of O content (Na 2 O / Li 2 O) is 5 or less, and Li relative to the total content of MgO and CaO 2 Molar ratio of O content (Li 2 O / (MgO+CaO)) is 0.03-0.4, Li 2 O, Na 2 O and K 2 SiO relative to the total O content 2 Molar ratio of content (SiO 2 / (Li 2 O+Na 2 O+K 2 O)) is 4-22, Al 2 O 3 SiO content 2 and ZrO 2 The molar ratio of the total content of (SiO 2 +ZrO 2 ) / Al 2 O 3) is 2-10, and TiO relative to the total content of MgO and CaO 2 and Al 2 O 3 The molar ratio of the total content of (TiO 2 +Al 2 O 3 ) / (MgO+CaO)) is 0.35-2, the molar ratio of the total content of MgO and CaO to the total content of MgO, CaO, SrO and BaO ((MgO+CaO) / (MgO+CaO+SrO+BaO)) is 0.7-1, the molar ratio of the BaO content to the total content of MgO, CaO, SrO and BaO (BaO / (MgO+CaO+SrO+BaO)) is 0.1 or less, B 2 O 3 , SiO 2 , Al 2 O 3 and P 2 O 5 P relative to the total content of 2 O 5 Molar ratio of content (P 2 O 5 / (B 2 O 3 +SiO 2 +Al 2 O 3 +P 2 O 5 )) can be 0.005 or less.

[0132] According to one embodiment, there is provided a magnetic recording medium substrate made of the above-mentioned glass for magnetic recording medium substrates.

[0133] In one embodiment, the magnetic recording medium substrate has a homogeneous composition on the surface and in the interior.

[0134] According to one embodiment, there is provided a magnetic recording medium having a magnetic recording layer on the magnetic recording medium substrate.

[0135] According to one embodiment, there is provided a magnetic recording and reproducing device including at least one of the above magnetic recording medium and the above glass spacer for a magnetic recording and reproducing device.

[0136] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by adjusting the composition as described in the specification to the glass compositions exemplified above, it is possible to produce a glass for a magnetic recording medium substrate and a glass spacer for a magnetic recording / reproducing device according to one embodiment of the present invention. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.

Claims

1. SiO 2 The content is 56 to 80 mol %, Li 2 The O content is 2.00 mol% or less, B 2 O 3 The content is 0 to 4 mol %, The total content of MgO and CaO (MgO+CaO) is 9 to 40 mol %, and Specific gravity is 2.75 g / cm 3 and a glass transition temperature of 650° C. or higher.

2. SiO 2 The content is 56 to 80 mol %, B 2 O 3 The content is 0 to 4 mol %, Li 2 O, Na 2 O and K 2 Li relative to the total content of O 2 Molar ratio of O content (Li 2 O / (Li 2 O+Na 2 O+K 2 O) is 0.50 or less, The total content of MgO and CaO (MgO+CaO) is 9 to 40 mol %, and Specific gravity is 2.75 g / cm 3 and a glass transition temperature of 650° C. or higher.

3. SiO 2 The content is 56 to 80 mol %, B 2 O 3 The content is 0 to 4 mol %, Li 2 Na content relative to O content 2 Molar ratio of O content (Na 2 O / Li 2 O) is 1.25 or more, The total content of MgO and CaO (MgO+CaO) is 9 to 40 mol %, and Specific gravity is 2.75 g / cm 3 and a glass transition temperature of 650° C. or higher.

4. Li 2 The glass of claim 2 having an O content of 2.00 mol % or less.

5. Li 2 The glass according to claim 3 , having an O content of 2.00 mol % or less.

6. Li 2 Na content relative to O content 2 Molar ratio of O content (Na 2 O / Li 2 3. The glass of claim 2, wherein MnO is greater than or equal to 1.

25.

7. Li 2 Na content relative to O content 2 Molar ratio of O content (Na 2 O / Li 2 5. The glass of claim 4, wherein MnO is 1.25 or greater.

8. SiO 2 The content is 56 to 80 mol %, Li 2 O content is 10 mol% or less, B 2 O 3 The content is 0 to 4 mol %, SiO 2 and Al 2 O 3 The total content (SiO 2 +Al 2 O 3 ) is 76.60 mol % or more, The total content of MgO and CaO (MgO+CaO) is 9 to 40 mol %, and Specific gravity is 2.75 g / cm 3 and a glass transition temperature of 650° C. or higher.

9. SiO 2 and Al 2 O 3 The total content (SiO 2 +Al 2 O 3 8. The glass according to claim 1, wherein the content of Cd is 76.60 mol % or more.

10. Li 2 O, Na 2 O and K 2 Total content of O (Li 2 O+Na 2 O+K 2 10. The glass according to claim 1, wherein O) is in the range of 2.5 to 10 mol %.

11. A magnetic recording medium substrate comprising the glass according to any one of claims 1 to 10.

12. A magnetic recording medium comprising the magnetic recording medium substrate according to claim 11 and a magnetic recording layer.

13. A magnetic recording and reproducing device comprising the magnetic recording medium according to claim 12 and a magnetic head.

Citation Information

Patent Citations

  • Crystallized glass, and crystallized glass substrate for information recording medium

    JP2013023420A

  • Glass composition, glass plate for chemical strengthening, tempered glass plate, and tempered glass substrate for display

    WO2015162845A1

  • glass

    JP2010064921A